2011
DOI: 10.1091/mbc.e11-07-0657
|View full text |Cite
|
Sign up to set email alerts
|

RalA and RalB differentially regulate development of epithelial tight junctions

Abstract: The closely related GTPases RalA and RalB are required for assembly of tight junction gate, but not fence, function. These activities depend on direct binding to the exocyst complex. Whereas RalA–exocyst complexes are required for exocytosis of junction proteins, RalB–exocyst complexes are required for endocytosis of these components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 51 publications
(75 reference statements)
5
41
0
Order By: Relevance
“…In metazoans, Ral GTPases (RalA and RalB) interact with both Sec5 and Exo84, and these interactions have been implicated in many processes, including cell migration, autophagy, neurogenesis and cancer (Brymora et al, 2001;Sugihara et al, 2002;Moskalenko et al, 2002Moskalenko et al, , 2003Polzin et al, 2002;Balakireva et al, 2006;Bodemann et al, 2011;Chen et al, 2006Chen et al, , 2007Chien et al, 2006;Hazelett et al, 2011;Lalli, 2009;Rosse et al, 2006). Cell fractionation studies have shown that Sec5 and Exo84 are in separate sub-complexes (Moskalenko et al, 2003), and structure analysis has demonstrated that Sec5 and Exo84 competitively bind to GTP-Ral (Jin et al, 2005).…”
Section: Ralmentioning
confidence: 99%
“…In metazoans, Ral GTPases (RalA and RalB) interact with both Sec5 and Exo84, and these interactions have been implicated in many processes, including cell migration, autophagy, neurogenesis and cancer (Brymora et al, 2001;Sugihara et al, 2002;Moskalenko et al, 2002Moskalenko et al, , 2003Polzin et al, 2002;Balakireva et al, 2006;Bodemann et al, 2011;Chen et al, 2006Chen et al, , 2007Chien et al, 2006;Hazelett et al, 2011;Lalli, 2009;Rosse et al, 2006). Cell fractionation studies have shown that Sec5 and Exo84 are in separate sub-complexes (Moskalenko et al, 2003), and structure analysis has demonstrated that Sec5 and Exo84 competitively bind to GTP-Ral (Jin et al, 2005).…”
Section: Ralmentioning
confidence: 99%
“…This regulation of vesicular trafficking controls various complex cellular functions such as polarized membrane formation, cytokinesis, tight junction formation, and tumor cell invasion [41][42][43][44] . RALB also interacts with Sec5 to activate the IκB kinase TBK1 [21,45] .…”
Section: Ras Mutation and Cancer Therapeuticsmentioning
confidence: 99%
“…2), similar to active RalA-enhanced axon extension involving the exocyst (Lalli and Hall, 2005). To determine whether RalA regulates neuroblast morphology and migration through the exocyst, we electroporated CA RalA or an Exo84-uncoupled CA RalA version (RalAQ72LA48W) (Fukai et al, 2003;Hazelett et al, 2011) and examined RMS neuroblasts 5 days later. To assess the specificity of the effects caused by Exo84-uncoupled RalA, we also electroporated CA RalA uncoupled from RalBP1 (RalAQ72LD49N), another Ral effector (Jullien-Flores et al, 2000;Lalli and Hall, 2005) (Fig.…”
Section: Deletion Of Rala Affects Neuroblast Orientation and Morpholomentioning
confidence: 99%
“…Small GTPases coordinate these events to establish cell polarity in response to intra-and extracellular cues (Mellman and Nelson, 2008;McCaffrey and Macara, 2009;Hall and Lalli, 2010). Among these, the Ras-like GTPase Ral, of which there are two isoforms, RalA and RalB, has emerged as an important polarity regulator in a variety of contexts, including basolateral membrane trafficking and tight junction formation in epithelial cells (Shipitsin and Feig, 2004;Hazelett et al, 2011), polarized migration of fibroblasts and cancer cells (Rossé et al, 2006;Spiczka and Yeaman, 2008) and tumorigenesis (Camonis and White, 2005;Lim et al, 2005;Oxford et al, 2005;Bodemann and White, 2008;Hazelett and Yeaman, 2012). During brain development, Ral is involved in asymmetric division of neuroblasts (Carmena et al, 2011), neuronal migration in the neocortex (Jossin and Cooper, 2011), neurite branching (Lalli and Hall, 2005) and activity-dependent spine growth (Teodoro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%